A modified PiBVD model for LAMB wave resonator. Issue 3 (March 2017) - Wang, Yong; Hong, Yan; Goh, Wang Ling; Mu, Xiaojing
ABSTRACT: The advances in semiconductor fabrication technologies have enabled the integration of Lamb‐wave resonator on silicon substrate. But such integration has led to additional parasitic effects to the Lamb‐wave resonators. The availability of an efficient equivalent‐circuit model is thus vital. This paper proposes a modified hybrid π‐type/Butterworth‐Van Dyke (PiBVD) model. Compared with the conventional PiBVD model, the modified PiBVD model accounts for the parasitic inductances of the bonding wires. It therefore provides better accuracy when characterizing Lamb‐wave resonators over a wide frequency range. Experiment results have also verified that the modified PiBVD model has better fitting on Y11 (input reflection factor in Y‐parameter matrix). This improvement is greatly beneficial for resonator analysis and circuit designs © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:703–706, 2017